Study on the Microbial Inactivation and Quality Assurance of Ultrasonic-Assisted Slightly Acidic Electrolyzed Water for Mirror Carp (Cyprinus carpio L.) Fillets During Refrigerated Storage - Qiang Zhong; Xiufang Xia; Fangfei Li (Foods)
The advancement of non-thermal disinfection technologies represents a critical pathway for ensuring food safety, meeting environmental sustainability requirements, and meeting consumer preferences for clean-label products. This study systematically evaluated the combined preservation effect of ultrasonic-assisted slightly acidic electrolyzed water (US+SAEW) on mirror carp fillets during refrigeration. Results demonstrated that US+SAEW exhibited superior antimicrobial efficacy compared to individual US or SAEW, achieving reductions of 0.73, 0.74, and 0.79 log CFU/g in total viable counts (TVC), Aeromonas bacteria, and lactic acid bacteria counts compared to the control, respectively. Furthermore, the combined intervention significantly suppressed microbial proliferation throughout the refrigeration period while simultaneously delaying protein and lipid degradation/oxidation induced by spoilage bacteria, thereby inhibiting the formation of alkaline nitrogenous compounds. Consequently, lower levels of pH, total volatile basic nitrogen (TVB-N), protein carbonyl, and thiobarbituric acid reactive substances (TBARS) were observed in US+SAEW compared to the other treatments. Multimodal characterization through low-field nuclear magnetic resonance (LF-NMR), texture, and color analysis confirmed that US+SAEW effectively preserved quality characteristics, extending the shelf life of mirror carp fillets by four days. This study provides a novel non-thermal preservation strategy that combines microbial safety maintenance with quality retention, offering particular advantages for thermolabile food.